The fractious nation? : unity and division in contemporary American life - Rieder, Jonathan; Steinlight, Stephen (University of California Press, 2003)
What are we to make of the speed with which the new climate of national solidarity emerged after September 11? Does it not look strange against a backdrop of the much-touted divisiveness of American life? In truth, The Fractious Nation? makes clear, the contrast of the time of divisiveness before and the time of unity that followed is much too stark, indeed.